The Role of Language Teaching in Promoting Educational Quality in Early Childhood Education - Wei, Wen; Mamat, Nordin Bin (South Asian Journal of Social Sciences and Humanities, 2024)
Background and purpose: China is among the countries putting great emphasis on  strengthening early education programs to ensure a solid learning foundation for children. The  present study is based on a qualitative research design to examine the role of English as a  Foreign Language (EFL) teaching in promoting educational quality in the context of early  childhood education in China. It focuses on investigating the effectiveness of EFL teaching in  enhancing the educational quality of early childhood education in the education system of  China. Method: The semi-structured interviews were conducted to assess the parents’  perception regarding the impact of EFL programs on the quality of education being offered in  early childhood centres in China. The sample for the survey was selected from the parents of  children enrolled in early childhood education centres in China offering EFL teaching as a part  of their curricula. The data collection focused on the student’s cognitive development and  overall quality of education. Findings: Most of the participants emphasized the significant  impact of early EFL education on their children’s cognitive skills. They regarded EFL  education as a robust tool to lay a strong foundation for future academic achievements and  cross-cultural understanding of their children. Conclusion and Implications: Thus, parents in  China regard early EFL education as crucial for the cognitive development and educational  foundation of their children. The present study offers significant pedagogical implications  regarding the inclusion of EFL instructions in enhancing the early language acquisition  experience of children.
Keywords: Language teaching; EFL; Educational quality; Early childhood education